The cultural industries in the French-speaking countries of sub-Saharan Africa : case of the Burkina Faso - (:unkn) unknown (My University, 2018)
THESIS SUMMARYAfrica is no exception to the debates on the cultural industries, already in vogue, at the global level. Although well developed in the North, cultural industries are less developed in Africa. In the continent, while some countries have successful models of development in this sector, like Nigeria or South Africa, the cultural industries in francophone countries of sub-Saharan Africa are still in a precarious level. This seems likely due to a late awareness of their issues, socio-political considerations, or a misunderstanding of the roles of the actors. Hence our interest in studying the role of public authorities in the process of cultural industries development in Burkina Faso, through the following subject: Cultural industries in francophone countries of sub-Saharan Africa: case of Burkina Faso. To carry out our reflection on the subject, the methodology consisted as well of a theoretical brusaillage and field investigations, allowing to confirm the hypotheses emitted.In Burkina Faso, the cultural industries are dynamic, by their organization, despite some shortcomings in the development of cultural sectors. This dynamic, favorable to the implementation of major initiatives and cultural events, makes the country as a "cultural crossroads" in Africa. Cultural industries generate considerable social, political and economic impacts for the country. However, these profits are the subject of conflicts between mainly industrial culture sector and the public sector. It is therefore essential that public authorities and cultural private sector work in synergy, with well-defined roles, to take the challenges seriously, for a more viable, dynamic and sustainable sector.
Keywords: African Research